Industrial Ergonomics Approach to Avoid Work Delays and Increase Work Productivity - Gempur Santoso (International Journal of Scientific Multidisciplinary Research, 2023)
Work delays are still common and result in less-than optimal productivity. The ergonomic approach emphasizes analysis to avoid work delays. Writing method based on literature study. The analysis and discussion use descriptive, namely the presentation of several opinions from the results of research by experts. Conclusion: a) several factors that result in work delays, namely: availability and expertise of labor, availability of tools, location/place of work, adequacy of salary, stage planning, communication, occurrence of work accidents, discipline and work motivation; b) at work, an ergonomic approach, namely tools made according to the user, a healthy company environment makes the workforce healthy, and psychologically good work motivation and all range of work becomes easy. So, it makes work not experience delays in work. By not working late, many products are produced, so that productivity is optimal. Suggestion: it is hoped that the industry (company) pays attention to all the factors that result in work delays to be corrected with an ergonomic approach, it will prevent work delays and work productivity will increase